From comrades-in-arms to “Swiss mercenaries.” The features of Argentine political-military emigration in the Estado Oriental del Uruguay (1838-1846) (Quinto Sol, 2018)
The article examines the incorporation process of the so-called “argentine emigration”, in war forces and political circles of Montevideo and its rural hinterland between 1838 and 1846. This phenomenon, full of tensions, had a strong impact on the reconfiguration of local identities and “parties”. Starting from a quantitative analysis about the volume of the military “emigration” this paper postulates that the construction of two officers’ groups in the Río de la Plata region – “Argentine” and “Oriental”- was in fact a slow and conflictive process and was still far from complete in the middle of the nineteenth century.
Keywords: war; emigration; regional history; Río de la Plata